Dry adhesion study of polyester/melamine clear coats on galvanized steel. (December 2019) - Greunz, T.; Lowe, C.; Schmid, M.; Wallner, G.M.; Strauß, B.; Stifter, D.
Abstract: The dry adhesion strength of polyester/melamine clear coats varying in their branching degrees were applied on galvanized steel panels and investigated by pull-off and T-bend testing. It was found that pull-off tensile adhesion is mainly dominated by the type of coating and less influenced by the pretreatment of the substrate. In contrast, the critical T-bend strain is mainly affected by the surface treatment of the galvanized layer with higher stiffness but lower ductility compared to the clear coat. Pull-off tensile strength at room temperature is correlating with the glass transition temperature Tg and a strong viscoelastic contribution is ascribed to the work of adhesion. Samples with adhesive as well as cohesive failure modes were further investigated by X-ray photoelectron spectroscopy (XPS) to determine the interfacial chemistry. Angle-resolved XPS data suggest that the nitrogen from the melamine crosslinker plays a decisive role for the adhesion of the coatings. Regarding the melamine distribution a micro- and a nanostructural effect has to be considered: while maximum melamine concentrations over coating depth are usually found in the bulk region of these clear coats, this work proposes that the remaining melamine at the interface segregates towards the metallic substrate. Highlights: Testing of dry adhesion was performed for 21 clear coat/substrate combinations. Fracture behaviour is dominated by the clear coat for pull-off testing. At room temperature adhesion correlates with the glass transition Tg. XPS analysis shows a correlation between fracture mode and interface structure. Melamine is considered to contribute to adhesive and cohesive properties.